Modern requirements to the professional training of the future primary school teacher in the process of education informatization - Онищенко, Ірина Володимирівна (Pedagogy of Higher and Secondary Education, 2016)
Onyshchenko I. V. Modern requirements to the professional training of the future primary school teacher in the process of education informatization. The article deals with peculiarities of the influence of the higher pedagogical education informatization on the process of the professional training of the future primary school teacher. The main professional qualities of the modern primary school teacher have been determined. The current requirements to the professional training of the primary school teacher in the process of education informatization have been grounded.